An efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications. Issue 10 (6th February 2015) - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V.
<x xml:space="preserve">Abstract</x> Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) for catalytic application.